PENGARUH KOMITMEN DAN JOB INSECURITY TERHADAP INTENSI TURNOVER PADA OPERATOR GARUDA CALL CENTER - Dinar Hendrayani (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: Every Company wants its employees have the ability to high productivity inwork. This is an ideal desire for profit-oriented companies, because how can a companymake a profit if it is filled in by people who are not productive. However, sometimescompanies are not able to distinguish which employees are productive and which are notproductive. Garuda Call Centre operators are contracted to work for one year under theEmployment Services Provider Company, and after it had conducted an evaluation todetermine whether the employees in question will resume contract or the contract may beterminated. This kind of employment contract system was influential on the level ofturnover. Result of research can be said a significant influence Commitment (X1) of theTurnover Intention (Y) with most dominant in dimension of faith in the managementwishes to move, the correlation value is 0.849, there is a significant effect of JobInsecurity (X2) on Turnover Intention (Y) with most dominant in dimension of the threatof job loss itself wishes desire and commitment to move (X1), the correlation value is0.829, and Job Insecurity (X2) are jointly significance influence on Turnover Intention(Y).Keywords: Commitment, Job Insecurity, Turnover Intention